1999
DOI: 10.1086/210137
|View full text |Cite
|
Sign up to set email alerts
|

Low Socioeconomic Status and Mental Disorders: A Longitudinal Study of Selection and Causation during Young Adulthood

Abstract: Over the past half century two competing hypotheses in sociological inquiry have provided interpretations of the well-documented association between low socioeconomic status and mental disorders. The selection hypothesis asserts that mental disorders impair status attainment, whereas the causation hypothesis states that conditions of life associated with low socioeconomic status markedly increase the risk of mental disorders. Using data from the longitudinal Dunedin Multidisciplinary Health and Development Stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

37
442
1
6

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 497 publications
(494 citation statements)
references
References 73 publications
37
442
1
6
Order By: Relevance
“…First, disorders that involve externalizing behavior are more consistently associated with termination of schooling across the four milestones than are disorders that involve internalizing behaviors. Neither major depression nor generalized anxiety disorder were associated with subsequent termination of schooling at any of the milestones examined, consistent with the findings of several longitudinal studies (Fergusson et al, 2002;Johnson et al, 1999;Miech et al, 1999). Second, the association of mental disorders with termination of schooling is more consistent across disorders with respect to high school than with respect to any of the other milestones examined.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…First, disorders that involve externalizing behavior are more consistently associated with termination of schooling across the four milestones than are disorders that involve internalizing behaviors. Neither major depression nor generalized anxiety disorder were associated with subsequent termination of schooling at any of the milestones examined, consistent with the findings of several longitudinal studies (Fergusson et al, 2002;Johnson et al, 1999;Miech et al, 1999). Second, the association of mental disorders with termination of schooling is more consistent across disorders with respect to high school than with respect to any of the other milestones examined.…”
Section: Discussionsupporting
confidence: 85%
“…On the other hand, studies examining impulse-control and substance use disorders have found associations with subsequent school termination that remain significant after accounting for childhood adversities. These effects have been found for conduct disorder (Miech et al, 1999), attention deficit disorder (Miech et al, 1999), overall externalizing behaviors (McLeod et al, 2004), overall disruptive disorders , and substance use disorders . However, no study has examined associations with school termination for a wide range of specific DSM disorders across the full range of educational milestones from primary school through college graduation.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…Finally, depression and tobacco dependence were more strongly linked to adult socioeconomic status than to childhood socioeconomic status (table), suggesting that proximal experiences in adulthood better account for the association between low socioeconomic status and these mental health disorders. 24 Several limitations are apparent. First, our measure of childhood socioeconomic origins was limited to parental occupational status and did not incorporate all potential indicators of social inequality.…”
Section: Discussionmentioning
confidence: 99%
“…Social causation has been most persuasively demonstrated with conditions of lesser severity, such as anxiety disorder. One long-term longitudinal study of New Zealand youth confirmed that although anxiety disorders are the outcome of social processes, both conduct and attention deficit disorders showed clear evidence of impacts on the educational careers of the youth (Miech, Caspi, Moffitt, Wright, & Silva, 1999). Both depression and personality disorders have most commonly been found to be outcomes of low SES; however, the reverse has also been found.…”
Section: Introductionmentioning
confidence: 99%